(untitled) (UUM Journal of Legal Studies, 2016)
This article demonstrates that the cases decided by the ICJ and the arbitration tribunals are judge made law and are not derived from the rules of customary law. Judge made law, as enunciated by the ICJ and the arbitration tribunals are very general and imprecise. The decisions made by the ICJ and the arbitration tribunals beget unpredictability or unexpected results. Normally, state parties are not happy with the decision made by the ICJ and the arbitration tribunals and the discontented states are unable to take any actions as state parties need to comply with the decision of the ICJ. In this Article, two (2) cases, one in South America and the other one in Africa, were discussed in detail. The outcome of these two (2) cases is not palatable to some state parties. Since the decisions are not predictable and the outcome is not palatable to some state parties, this Article looks at possible solutions which are being offered in International Islamic Law (Siyar). Keywords: Islamic International Law (Siyar), International Court of Justice (ICJ), Judge Made Law, Maritime Boundary Delimitations, Unpredictable Results, The Principle of Joint Administration, The Principle of Joint Development.